2013
DOI: 10.1177/1363461513487665
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing mental health providers’ intention to use telepsychotherapy in First Nations communities

Abstract: Telemental health is the use of information and communications technologies and broadband networks to deliver mental health services and support wellness. Although numerous studies have demonstrated the efficiency and utility of telemental health, certain barriers may impede its implementation, including the attitudes of mental health service providers. The current study draws on the technology acceptance model (TAM) to understand the role of mental health service providers' attitudes and perceptions of teleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 46 publications
4
42
1
1
Order By: Relevance
“…The majority of measures were developed in the USA ( n  = 28), with Canada and Australia also having developed three or more measures each. Sixteen measures were developed for use in school settings [3852], six for use in universities or colleges [5360], three for use in pharmacies [6163], two for use in police or correctional facilities [64, 65], two for use in nursing homes [66, 67], six for use with whole communities or in multiple settings [6875], and sixteen measures were developed for use in workplace settings or other organisations (e.g. utility companies, IT service providers, human services) [7692].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of measures were developed in the USA ( n  = 28), with Canada and Australia also having developed three or more measures each. Sixteen measures were developed for use in school settings [3852], six for use in universities or colleges [5360], three for use in pharmacies [6163], two for use in police or correctional facilities [64, 65], two for use in nursing homes [66, 67], six for use with whole communities or in multiple settings [6875], and sixteen measures were developed for use in workplace settings or other organisations (e.g. utility companies, IT service providers, human services) [7692].…”
Section: Resultsmentioning
confidence: 99%
“…The internal structure of 45 instruments was determined via EFA (11 of these also used CFA [42, 49, 52, 54, 55, 59, 65, 67, 77, 78, 82, 9193]), and six studies used CFA alone [39, 40, 68, 72, 75, 83, 94] (Additional file 3). For studies which conducted EFA, 46 % reported that >50 % of the variance was explained by the final factor model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations